Creation of educational games — Project based learning in e-Learning systems course - Jovanov, Mile; Ilijoski, Bojan; Stankov, Emil; Armenski, Goce (IEEE, 2017)
In this paper we present a successful example of implementation of project-based learning in e-Learning Systems course. Starting with an overview of the organization of the “e-Learning Systems” course held at the Faculty of Computer Science and Engineering (FCSE) in Skopje, we look into the importance of project-based learning as a learning method, the benefits of team work, and also we describe the purpose of educational games. The paper focuses on the general form of the project assigned to students which we describe in details, the organization of the lab exercises and the process of implementation of the projects. Based on the results that we will present, we may conclude that we have managed to organize the course in such a way that many of the students will achieve the course goals and pass, and also, will have exciting and challenging project to work on. We believe that the material in this paper will be valuable to other lecturers that teach similar or even quite different courses, and also facing the problem of teaching a course with high student/teacher ratio.
Keywords: project-based learning; e-learning systems course; educational games development